TRANSLATION OF WORDS CONTAINING LOCAL CULTURAL ELEMENTS OF MANADO MALAY LANGUAGE INTO JAPANESE (TRANSLATION ANALYSIS) - Monoarfa, Stanly (Universitas Hasanuddin, 2024)
The combination of the Manado Malay language in North Sulawesi with the Japanese language is a research that examines language teaching that focuses on the study of vocabulary translation which is one of the fields of applied linguistics involving two language elements, namely Manado Malay language and Japanese language. By using the survey method through informants, the researcher will go to the field to find native speakers of Manado-Minahasa who can be used as sources, knowing a lot about the local language words that contain as many cultural elements. It is hoped that the translation results can be used for the development of the world of tourism, especially encouraging Japanese tourists to visit North Sulawesi which has many Manado cultural elements and the fulfillment of Unsrat's strategic plan in realizing a superior and cultured University.